Footwear‐Generated Dynamic Biomechanical Manipulation and Perturbation Training for Chronic Nonspecific Low Back Pain. Issue 8 (21st February 2018) - Lee, Se Won; Veeramachaneni, Ratnakar; Saleh, Ibrahim Abou; Morice, Karen; Tiu, Timothy; Lo, Yungtai; Frison, Kevin; Bartels, Matthew N.
Abstract: Background: Home‐based therapy optimizing biomechanics and neuromuscular control is increasingly recognized as a treatment option for chronic nonspecific low back pain (CNSLBP). However, its impact on pain, function, and gait is limited among patients in a metropolitan area. Objective: To evaluate the change of pain, function, and gait parameters with home‐based therapy with the use of footwear‐generated biomechanical manipulation and perturbation training in a population with CNSLBP in a metropolitan area. Design: Prospective observational study. Setting: Outpatient rehabilitation clinic at an academic teaching hospital. Participants: One hundred sixteen patients with CNSLBP for more than 6 months. Intervention: Six months of home‐based therapy with a biomechanical device using 4 modular elements attached to a foot‐worn platform. Main Outcome Measures: Instrumental gait analysis (gait velocity, step length, single limb support phase % of gait cycle), Numeric Rating Scale for pain, and Oswestry Disability Questionnaire Index for pain and function. Results: Only 43 patients (37.1%) completed the study. Among 43 patients, mean gait velocity increased from 86.6 ± 20.7 to 99.7 ± 22.1 cm/s ( P < .0001) in 6 months. Mean left step length increased from 51.1 ± 8.4 to 54.8 ± 9.8 cm ( P < .0001). Mean right step length increased from 51.0 ± 7.9 to 55.4 ± 9.0 cm ( P < .0001). Mean single limb support increased from 36.4 ± 2.8 to 37.2 ± 2.5%, ( P = .208) in the right side and from 36.6 ± 3.0 to 37.8 ± 4.4%, ( P = .019) in the left side. Median Oswestry Disability Questionnaire Index score improved from 28 (18‐44; interquartile range) to 17 (10‐35) ( P = .045). Mean Numeric Rating Scale for back pain improved from 7.7 ± 1.8 to 3.3 ± 3.1 ( P < .0001). Conclusion: At 6 months, patients with CNSLBP undergoing home‐based therapy with footwear‐generated biomechanical manipulation and perturbation training demonstrated significant improvement of objective gait parameters, pain, and function. Level of Evidence: IV